Seismicity of the western-Svalbard margin and its relationship with near surface fluid flow and seepage systems - A study using ocean bottom seismometers - Domel, Przemyslaw (UiT Norges arktiske universitet, 2023)
Methane, a high potential greenhouse gas, travels as a fluid and releases as a gas in large quantities from the seafloor. This seepage impacts marine ecosystems and in specific cases, it has potential to reach the atmosphere, and therefore affect the climate. Gas seepage is documented worldwide, but there are still large unknowns regarding seepage dynamics, faulting/fracturing of the sediments and the corresponding seismic response. In this thesis, we investigated seismological signals recorded on the seafloor on the west Svalbard continental margin to improve our understanding of processes controlling fluid flow in the shallow sediments. We used three ocean bottom seismometer datasets that recorded seismic signals offshore Svalbard, close to known gas seepage locations, such as the Vestnesa Ridge contourite drift. We studied both local, micro seismic signals that may be connected to near-seafloor fluid flow and earthquake distribution in the region to infer information about the current state of stress that is affecting the sediments. Throughout this work, we developed a machine learning based approach for the recognition of seismological signals recorder locally at the seafloor. We found an indirect link between micro seismicity and changes in the seafloor pressure caused by ocean tides and established a methodology that can be used to further investigate this link using new datasets in the future. Earthquake observations near the Knipovich Ridge and Molloy Transform Fault showed that shallow fracture systems can be potentially influenced by the deeper crust, which formed through seafloor spreading at obliquely spreading mid-ocean ridges. The same analysis revealed new local regions of seismicity close to the plate boundaries that deserve further investigation. This work demonstrates that passive seismic observations can complement other geophysical methods in improving our understanding of complex mechanisms that control subseafloor fluid flow systems not only in the Arctic, but in other sedimentary basins ...